2016
DOI: 10.1016/j.renene.2016.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of two Pumps As Turbines for hydropower generation

Abstract: In recent years, the use of turbines or Pumps operating As Turbines (PATs) has been proven to be a sustainable alternative for managing Water Distribution Networks (WDNs), by coupling pressure control and leakage reduction with hydropower generation.\ud Pumps running in reverse mode can be an effective alternative to using turbines for energy production in WDNs. Many commercial models are readily available on the market and a number of economic and technical advantages for installation, operation and maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 19 publications
0
61
0
1
Order By: Relevance
“…(5) was adopted to define the complete characteristic curve of the PAT obtained by [32,33] testing four centrifugal pumps in turbine mode; moreover the Eq. (5) was verified by Pugliese et al [18] with a good agreement for a single-stage Lowara pump:…”
Section: Pat Working Conditionmentioning
confidence: 63%
See 1 more Smart Citation
“…(5) was adopted to define the complete characteristic curve of the PAT obtained by [32,33] testing four centrifugal pumps in turbine mode; moreover the Eq. (5) was verified by Pugliese et al [18] with a good agreement for a single-stage Lowara pump:…”
Section: Pat Working Conditionmentioning
confidence: 63%
“…In the last few years, interesting and numerous efforts have been dedicated to unravelling the knot and to define general equations able to transpose the characteristic curve of a pump to the correspondent in reverse mode, adopting experimental set-up [18,19], computational fluid dynamics applications (CFDs) [20][21][22], literature data [23], or proposing new devices [24]. Jain and Patel [25] presented a detailed state of the art about this aspect; several researchers, with the aim to analyze the behavior of a pump in a turbine mode, had defined several and sometimes really different relations for the prediction of PAT efficiency, based on specific speed in pump mode.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure is regulated with a valve installed at the network inlet, while the flow rate at the outlet is varied with a butterfly valve. Valves are remotely controlled with electronic actuators controlled by a dedicated homemade software program, with an external PLC [34][35][36][37][38][39][40]. The electric motor of the pump is linked to an inverter and the produced electrical power is connected to the urban power grid.…”
Section: Ns 376 Pump Model Validation With Experimental Datamentioning
confidence: 99%
“…Some studies demonstrate that the use of PATs, instead of classic turbines, to substitute the dissipation valves could be a convenient practice even if the available power is low, due to the low price and the mechanical simplicity of such devices [33]. Several studies have shown that the best efficiency of a PAT could be greater than 70% [21][22][23]. Ramos et al [34] showed that the cost of a PAT is much smaller if compared with the cost of a classic turbine, with unit costs ranging between 200 e /kW and 400 e /kW, where the turbine cost ranges between 300 e /kW and 800 e /kW.…”
Section: Energy Recovery In Water Systemsmentioning
confidence: 99%
“…Three main problems limit the convenience of the installation of a turbine governed generator to power the pumping system, namely (i) the small amount of power available; (ii) the high cost of traditional turbines; and (iii) the low combined efficiency of the two electromechanical devices (the turbine generator and the pump motor) [18][19][20]. PATs could be employed instead of classic turbines, since they are considered a viable and flexible solution for energy production in a WDN, due to their lower cost and their generally acceptable efficiency [21][22][23][24]. In order to reduce the investment cost and increase the efficiency of the system, the PAT and a pump can be directly coupled and mounted on the same shaft without any intermediate generator or motor.…”
Section: Introductionmentioning
confidence: 99%